Analysis of first plus recurrent cardiovascular (CV) and hospitalisation events in the CAROLINA trial. (25th November 2020) - Marx, N; McGuire, D.K; Johansen, O.E; Rosenstock, J; Pfarr, E; Mattheus, M; George, J.T; Espeland, M.A; Zinman, B
Abstract: Background/Introduction: CAROLINA (cardiovascular outcome study of linagliptin versus glimepiride in type 2 diabetes) was a randomised controlled clinical trial designed to compare the effects of linagliptin with glimepiride on CV events and other outcomes in patients with relatively early type 2 diabetes at elevated CV risk. Purpose: To characterise the effects on net CV disease and the hospitalisation burden of this population, we assessed the effects of linagliptin vs glimepiride on all first plus recurrent CV events and all cause hospitalisations. Methods: Participants with relatively early type 2 diabetes, high CV risk and HbA1c 6.5–8.5% were randomized to linagliptin 5 mg or glimepiride 1–4 mg once daily on top of standard of care. Cox regression was used to produce hazard ratios for time to first event. A negative binomial model was used to produce event rate ratios for all events. Results: A total of 6033 participants were enrolled (mean age 64.0 years, HbA1c 7.2%, body mass index 30.1 kg/m 2, eGFR 77 ml/min/1.73 m 2, median type 2 diabetes duration 6.3 years, urine albumin:creatine ratio 10 mg/g, 42% with CV disease, 4.5% with heart failure). Adding recurrent events increased the number of events for analysis from first event by 10% more to 77% across CV/heart failure outcomes and by 119% for all cause hospitalisations, with corresponding increases in rates per 100-patient years in both treatment groups (e.g. for the composite of CV death/MI/stroke from 2.1 to 2.8 for linagliptin and 2.1 to 2.9 for glimepiride) over a median follow up of 6.3 years. Results of analyses of first-event and first plus recurrent events are presented below (Fig). Conclusion: No significant differences were observed between linagliptin and glimepiride for either first or first + recurrent CV or hospitalisation events. These data underscore the significant CV disease burden experienced even in relatively early type 2 diabetes and reinforce the similar CV safety between linagliptin and glimepiride, differing only on hypoglycaemia risk. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boehringer Ingelheim and Eli Lilly and Company